Expanding the phenotype of Bruck syndrome: Severe limb deformity, arthrogryposis, congenital cardiac disease and pulmonary hemorrhage. Issue 1 (25th October 2022) - Sandy, Jessica L.; Perez, Darazel; Goh, Shuxiang; Forsey, Jonathan; Rajagopalan, Sulekha; Trivedi, Amit; Munns, Craig F.
Abstract: Bruck syndrome is a rare collagen disorder with autosomal recessive inheritance caused by pathogenic variants in either FKBP10 or PLOD2 genes. It is characterized by bone fragility and fractures similar in severity and variability to osteogenesis‐imperfecta as well as congenital joint contractures. This article describes an infant with a homozygous (partial) gene deletion of PLOD2 that includes the start codon and would be expected to lead to nonfunctional protein product. The infant had a severe phenotype of Bruck syndrome and is the only reported case of Bruck syndrome with congenital cardiac disease (triscuspid valve dysplasia with severe regurgitation, mitral valve prolapses with moderate regurgitation, and pulmonary hypertension) and pulmonary hemorrhage. We hypothesize that the additional feature of congenital cardiac disease in this case was due to the underlying defect in type I collagen, and that the pulmonary hemorrhage was multifactorial, with underlying vessel fragility, rib fractures, and high pulmonary pressures likely to be major contributing factors. Management was largely supportive with the use of bisphosphonates to assist in pain management. Care was complicated by comorbid cardiopulmonary compromise, limited evidence‐base guiding care, and difficulties in discussing end‐of‐life care.